Respons Pertumbuhan Sawi Hijau (Brassica juncea L.) terhadap Aplikasi POC Berbasis Daun Gamal (Gliricidia sepium) - Badi'ah, Baiq Arriyadul; Husnul Jannah; Sri Nopita Primawati (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
Gliricidia leaves are rich in nitrogen, phosphorus, and potassium, which are essential nutrients for plant growth. This makes Gliricidia leaves a potential raw material for liquid organic fertilizer (LOF). Therefore, this study was conducted to determine the optimal dosage of Gliricidia leaf LOF that can be applied to enhance the growth of Green Mustard (Brassica junceaL.). The study used a Completely Randomized Design (CRD) with five treatments. The treatments consisted of a control (P0), 30 ml LOF/liter (P1), 60 ml LOF/liter (P2), 90 ml LOF/liter (P3), and 130 ml LOF/liter (P4). The observed parameters included plant height (cm), number of leaves (leaves), and leaf width (cm) at 7, 14, 21, and 28 days after planting (DAP). The data were analyzed using ANOVA followed by the Least Significant Difference (LSD) test at the 5% level, using SPSS 20 software. The results showed significant effects on plant height, number of leaves, and leaf width between the control and each dosage of Gliricidia leaf LOF. The dosage of 130 ml LOF/liter resulted in the highest average growth in plant height, number of leaves, and leaf width compared to the control and the 30, 60, and 90 ml LOF/liter treatments. Therefore, it is concluded that applying 130 ml of Gliricidia leaf LOF per liter of water is recommended to enhance the growth of Green Mustard.